Integrating Entrepreneurship, Green HRM, and Innovation for Sustainable Performance in E- Business: Insights from Pakistan - Sh. M. Fakhre Alam Siddiqui; Hammad Zafar; Batool, Najia (Dialogue Social Science Review (DSSR), 2025)
This study examines the relationship between sustainable performance in e-business organizations and innovation, entrepreneurship, and green human resource management (HRM).The findings demonstrate the beneficial effects of green HRM, entrepreneurship, and innovation on sustainable performance. The largest impact is attributed to entrepreneurship, which is followed by innovation and green HRM. For long-term success, these findings emphasize how critical it is to foster an entrepreneurial culture, embrace cutting-edge procedures, and put green HRM ideas into reality. By demonstrating how these elements interact to affect sustainable performance, the study advances previous research by utilizing data from Pakistani e-business enterprises. The implications suggest that managers should enhance entrepreneurial activities, foster innovation, and apply green HRM practices to achieve sustainable performance. Policymakers should also support these practices in the digital economy. Further research is needed to understand how these elements work together in different contexts and industries.